Applying artificial neural networks in slope stability related phenomena - Tsangaratos, P.; Benardos, A. (Bulletin of the Geological Society of Greece, 2013)
Over the past years, Artificial Neural Networks (ANN) have been successfully used for the modelling in a great number of geoscience applications. In this paper we discuss the architecture and the way ANN work, presenting a specific learning algorithm which has been applied in the estimation of landslide susceptibility within a GIS environment.